Rapid Sequence Spinal pada Seksio Sesarea Emergensi - Adiyanto, Bowo; Widodo, Untung; Wibowo, Arif Setyo (Jurnal Komplikasi Anestesi, 2021)
Obstetric emergencies are a challenge both for the obstetrician and the anesthesiologist. The incidence of caesarean sections as per the National Family Health Survey published in 2015–16 was 17.2%. In 7.6% of cases, the decision to conduct a caesarean section was taken after the onset of labour pain. Caesarean sections are classified depending on the urgency into four categories. The target decision to delivery interval for category 1 caesarean section is less than 30 min. The management of these emergencies involves a rapid assessment with minimal investigations. Although general anaesthesia is considered to have higher morbidity and mortality, category 1 caesarean sections may still warrant this technique. Rapid sequence spinal anaesthesia is replacing general anaesthesia for category 1 SC emergency. In category 2 and 3 caesarean sections, spinal anaesthesia still remains the technique of choice